Evaluation of two treatment concepts of four implants supporting fixed prosthesis in an atrophic maxilla: finite element analysis - Anlin Li; Zhixiang Mu; BaiRui Zeng; Tianxi Shen; Rongdang Hu; Huining Wang; Hui Deng (BMC Oral Health, 2023)
Abstract Background Currently, oblique placement of long implants or the use of short implants to circumvent the maxillary sinus area and provide support for fixed prostheses are viable alternatives. The purpose of this study was to compare these two treatment concepts and ascertain which one exhibits superior biomechanical characteristics. Methods Two different treatment concept models were constructed. The first one, LT4I, consisting of two mesial vertical implants positioned in lateral incisor regions and two distal tilted implants (45°) situated in second premolar regions of the maxilla. The second model, VS4I, includes two mesial vertical implants in lateral incisor regions and two vertically positioned short implants in second premolar regions. Numerical simulations were conducted under three loading types: firstly, oblique forces upon the molars; secondly, vertical forces upon the molars; thirdly, oblique forces upon the incisors. The maximum principal stress (σmax) and minimum principal stress (σmin) of the bone, as well as von Mises stress of the implants, were calcuated. Results Under oblique loading on the molar, higher stress values in the bone were observed in LT4I group. Under vertical loading on molar, higher stress values in the bone were also observed in LT4I group. Furthermore, little difference was found between the two groups under oblique loading on the incisor. Conclusion Both treatment concepts can be applicable for edentulous individuals with moderate atrophic maxilla. Compared to tilted implants, short implants can transmit less occlusal force to the supporting tissues.